Victim Blame in Fictional Crime Dramas: An Examination of Demographic, Incident-Related, and Behavioral Factors. Issue 1 (1st January 2016) - Rader, Nicole E.; Rhineberger-Dunn, Gayle M.; Vasquez, Lauren
Abstract : How victims are portrayed in fictional crime dramas is an important way that individuals come to understand and interpret what it means to be a victim of crime. We examine how demographic variables (e.g., gender, race, age), incident variables (e.g., location of offense, relationship between victim and offender, type of crime), and behavioral variables (e.g., drug use/alcohol use, sexual promiscuity, negative personality traits, or concealing elements of personality) predict victim blame. Although some literature has analyzed victims in fictional crime dramas, such literature has been limited to a single year, a single show, a particular crime, or a particular factor. We extend this literature by focusing on multiple factors that predict victim blame using data collected from a systematic sample of 124 episodes from 4 fictional crime dramas ( CSI, Law & Order: Special Victims Unit, Criminal Minds, and Without a Trace ) over 7 years (2003–2010).